Analysis of Students' Motor Educability Ability in Rural - Bagus Sri Nurhafis; Rubiyatno Rubiyatno; Y. Touvan Juni Samodra; Eka Supriatna; Putra Sastaman (Sriwijaya Journal of Sport, 2024)
Motor educability is a movement repertoire that functions to learn new movements. This can be seen from how motor educability is carried out. The aim of this research was to determine the motor educability of elementary school students in grades 1, 2 and 3 who attend schools in rural areas. The important reason for researching with a sample of students who attend school in rural areas is as proof, whether it is true that by living in a village with more opportunities to move, their movement abilities will also be good. This research uses survey methods, quantitative research. The sample consisted of 138 students consisting of 83 boys and 55 girls. The measurement test uses the IOWA BRACE TEST which consists of 21 types of tests. The research data were analysed using Excel and presented in the form of a measure of central tendency. Based on the calculation results obtained as follows. The average results of motor skills educability are relatively the same between boys and girls, namely with a mean score of 28.75 for boys and 28.09 for girls. Judging from the status, 4% are in the very poor category, 13% are poor, 62% are moderate, 13% are good and only 8% are very good. These results show that there are still very few students who have motor educability skills in the good and very good categories (13% and 8%). On average, the motor skills of village school students are in the medium category.